2021
DOI: 10.1515/cclm-2021-0566
|View full text |Cite
|
Sign up to set email alerts
|

Harmonization status of procalcitonin measurements: what do comparison studies and EQA schemes tell us?

Abstract: Sepsis represents a global health priority because of its high mortality and morbidity. The key to improving prognosis remains an early diagnosis to initiate appropriate antibiotic treatment. Procalcitonin (PCT) is a recognized biomarker for the early indication of bacterial infections and a valuable tool to guide and individualize antibiotic treatment. To meet the increasing demand for PCT testing, numerous PCT immunoassays have been developed and commercialized, but results have been questioned. Many compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…So far, neither a reference material to standardize and trace PCT measurements, nor a higher-order reference method exist to quantify the absolute amount of PCT in human samples. The current heterogeneity of PCT measurements in clinical diagnostics is also reflected by the regular monitoring of national external quality assessment programs (EQAs) [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, neither a reference material to standardize and trace PCT measurements, nor a higher-order reference method exist to quantify the absolute amount of PCT in human samples. The current heterogeneity of PCT measurements in clinical diagnostics is also reflected by the regular monitoring of national external quality assessment programs (EQAs) [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Despite PCT's high relevance for sepsis diagnosis, evaluation of analytical performance and comparability of results of the different commercially available immunoassays for PCT have rendered conflicting results. 21 The need for harmonization of PCT quantification results has been highlighted, 22,23 yet neither reference material to standardize and trace PCT measurements nor an orthogonal method of higher order of reference exists. 21,24 Activities to harmonize and standardize PCT quantification are currently ongoing by the PCT working group of the International Federation of Clinical Chemistry (IFCC WG-PCT).…”
Section: ■ Introductionmentioning
confidence: 99%
“…21 The need for harmonization of PCT quantification results has been highlighted, 22,23 yet neither reference material to standardize and trace PCT measurements nor an orthogonal method of higher order of reference exists. 21,24 Activities to harmonize and standardize PCT quantification are currently ongoing by the PCT working group of the International Federation of Clinical Chemistry (IFCC WG-PCT). 25 To our knowledge, only three studies using LC−MS/MS for quantification of PCT in human serum have been reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the source of such variability remains unclear. 12 A proposed route to improve comparability and accuracy of the results is developing reference calibration materials, which have been value-assigned with a higher-order reference measurement procedure (RMP). 13 − 15 Such a higher-order reference measurement system is still missing for PCT.…”
mentioning
confidence: 99%
“…Different studies underlined discrepancies of results provided by various commercially available PCT assays. These discrepancies may impact clinical decisions at cut-offs, leading to disease misclassification and inappropriate antibiotic treatment decision. However, the source of such variability remains unclear . A proposed route to improve comparability and accuracy of the results is developing reference calibration materials, which have been value-assigned with a higher-order reference measurement procedure (RMP). Such a higher-order reference measurement system is still missing for PCT.…”
mentioning
confidence: 99%